CO27: Refocusing the world on the energy transition agenda - James Henderson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2022)
In this latest edition of the Oxford Energy Forum we include a series of 18 articles on issues relevant to the upcoming discussions at COP27, which will be held in Egypt in November 2022. The articles cover a wide range of issues, starting with the current state of environmental diplomacy in the wake of the global geopolitical turbulence caused by Russia's invasion of Ukraine. We then address the perspectives of multiple actors ahead of the conference, focussing in particular on the divergent views between countries from the developed and developing world. In particular we reflect the emerging dissatisfaction of countries from the Global South and the need for countries from the developed world to provide the finance and technology that have been promised before but not delivered. We also look at various other important topics such as the development of new technologies, the global methane pledge, green finance, the prospects for nuclear power and hydrogen, and the development of carbon markets and consider how they will be discussed as part of the COP process. The overall aim is for this edition of the OEF to be an important primer ahead of COP27, to provide readers with an overview of the key issues which will determine the success or failure of the negotiations in Sharm El-Sheikh.
Keywords: 330